A nanodiamond for structural biomimetic scaffolds - Aversa, Raffaella (Array, 2019)
Bio-mechanically active scaffolds for tissue engineering combining hydrophilic polymeric matrix and nano-diamond fillers properties are presented and discussed in this paper. The resulting scaffolding materials revealed remarkable mechanical and biological properties to be exploited in advanced biomedical applications. The novel hybrid material is based on 2 and 5 volume % of detonation nano-diamond particles in a hydrophilic poly-(hydroxyl-ethylmethacrylate) matrix. According to its mechanical and biological properties, the nanocomposite shows a hybrid nature. The base analytical procedures for the preparation of the hybrid nanocomposites and some preliminary mechanical characteristics are presented. The proposed hybrid system has been considered for potential biomimetic, osteoconductive and osteoinductive scaffolds application in bio-mechanically active bone scaffolds for osteoblast and stem cell differentiation and growth. These more rigid hybrid nano-composites are predicted to possess improved mechanical strength overcoming the mechanical weaknesses of traditional hydrogels clinically utilized for bone regeneration.